Dynamic Deployment for Context-Aware Multimedia Environments - Duarte, Paulo Artur de Sousa; Silva, Luís Fernando Maia; Gomes, Francisco Anderson de Almada; Viana, Windson; Trinta, Fernando Antonio Mota (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
A current challenge of mobile computing is the need to an infrastructure that, in development-time, allows applications can dinamically adapt itself to the scenario. One of approaches that allows this infrastructure is the component-based middleware platforms use. An example of middleware is LoCCAM, intended for devices with Android operating system. This paper presents the LoCCAM evolution. Now, LoCCAM perform dinamically deploy of new components according to changes in the environment. We aim to make LoCCAM an infrastructure capable of providing support for mobile multimedia systems in IoT scenario. Dynamic deployment also enables applications to adapt dynamically to different versions of Android OS. We had create an application that uses mobile augmented reality based contextaware concepts as case study. We tested this application in two smartphones with different Android versions and one smartwatch with Android Wear.